2021
DOI: 10.1186/s13049-021-00955-6
|View full text |Cite|
|
Sign up to set email alerts
|

Use of troponin assay after electrical injuries: a 15-year multicentre retrospective cohort in emergency departments

Abstract: Background Patients with electrical injury are considered to be at risk of cardiac arrhythmia. Assessing the risk of developing a major adverse cardiac event (MACE) is the cornerstone of patient management. The aim of this study was to assess the performance of initial troponin and troponin rise to predict Major Adverse Cardiac Events (MACEs) in all patients with electrical injuries admitted to the Emergency Department. Methods This is a multicentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Following the publication of the original article [ 1 ] the authors brought to our attention that their first and last names had unfortunately been interchanged.…”
Section: Correction To: Scand J Trauma Resusc Emerg Med (2021) 29:141 101186/s13049-021-00955-6mentioning
confidence: 99%
“…Following the publication of the original article [ 1 ] the authors brought to our attention that their first and last names had unfortunately been interchanged.…”
Section: Correction To: Scand J Trauma Resusc Emerg Med (2021) 29:141 101186/s13049-021-00955-6mentioning
confidence: 99%
“…Similarly, Douillet et al . [5] found that troponin assay could refine risk-stratification in high-risk patients, defined as previously known heart disease, exposure to a high voltage of at least 1000 V, initial loss of consciousness, or abnormal initial ECG.…”
mentioning
confidence: 99%